2021
DOI: 10.1016/j.biopha.2021.111753
|View full text |Cite
|
Sign up to set email alerts
|

New epigenetic players in stroke pathogenesis: From non-coding RNAs to exosomal non-coding RNAs

Abstract: Non-coding RNAs (ncRNAs) have critical role in the pathophysiology as well as recovery after ischemic stroke. ncRNAs, particularly microRNAs, and the long non-coding RNAs (lncRNAs) are critical for angiogenesis and neuroprotection, and they have been suggested to be therapeutic, diagnostic and prognostic tools in cerebrovascular diseases, including stroke. Moreover, exosomes have been considered as nanocarriers capable of transferring various cargos, such as lncRNAs and miRNAs to recipient cells, with prominen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 252 publications
(242 reference statements)
0
14
0
Order By: Relevance
“…It has been found that lncRNAs are critical for angiogenesis and neuroprotection. Therefore, lncRNAs were considered as therapeutic, diagnostic and prognostic tools in cerebrovascular diseases, including stroke [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that lncRNAs are critical for angiogenesis and neuroprotection. Therefore, lncRNAs were considered as therapeutic, diagnostic and prognostic tools in cerebrovascular diseases, including stroke [17].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on formation and functional mechanisms of lncRNAs have shown that lncRNAs play a key role in regulating chromatin dynamics, gene expression and maintaining biological processes [14][15][16]. More and more evidences indicate that the dysregulation of lncRNA expression is closely related to the development of several human diseases, such as diabetes, sepsis, stroke, autoimmune diseases and cancer [8,[17][18][19][20][21]. Studies on tumors have shown that lncRNAs are involved in the pathogenesis of digestive system tumors through the regulation of autophagy [1].…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are one of the most important types of non-coding RNAs contained in sEV. These short (ca.22 nucleotide) non-coding RNAs are known as molecules able to repress and degrade target mRNAs, thus silencing gene expression [ 178 ]. miRNAs originate from polymerase II (Pol II)–synthesized, mRNA-like primary transcripts subsequently processed by the nuclear ribonuclease Drosha.…”
Section: Liquid Biopsy With the Use Of Sev In Solid Organ And Tissue Transplantationmentioning
confidence: 99%
“…The non-coding RNAs (ncRNAs) belong to a class of RNAs, which function at the RNA level ( Nicoloso and Calin, 2008 ; Pop et al, 2018 ). NcRNAs are highly heterogeneous in length, structure and cellular function ( Hashemian et al, 2020 ; Mirzaei and Hamblin, 2020 ; Balandeh et al, 2021 ; Dashti et al, 2021 ; Mahjoubin-Tehran et al, 2021 ). They can be classified into two main classes: structural non-coding RNA and regulatory non-coding RNA.…”
Section: Introductionmentioning
confidence: 99%